Experimental study and theoretic analysis of shear failure mechanism for short precast bridge columns with grouted splice sleeve (GSS) connectors under direct shear load. (1st December 2022) - Qu, Hongya; Lv, Hao; Zhang, Tao; Li, Tiantian; Wang, Zhiqiang
Highlights: Five short precast columns with different connection are tested under direct shear. Shear failure mechanism is investigated and compared for all column specimens. A new theoretic method is proposed to estimate shear strength for precast columns. The proposed theoretic model can effectively predict shear strength at various stages. Abstract: Precast bridge structures have been increasingly applied in recent civil engineering applications, which shortens construction time, lowers cost, improves structure quality, decreases traffic interruption, and reduces environment pollution. However, studies regarding to the shear behavior of short precast columns are limited. In this study, five short precast bridge columns, with span-to-depth ratio of 0.43, are tested under direct shear load. This is to understand shear failure mechanism of precast bridge columns with different design details. Two types of shear failure are found due to different embedment location of grouted splice sleeve (GSS) connectors. Different design details (e.g. steel grade of rebar, bonding material of joint interface, and existence of shear keys) also have certain impact on the shear strength of precast columns. Based on the test results, a new theoretic method is proposed to estimate shear strength of tested precast column specimens. The proposed method incorporates possible influencing factors of shear strength along with different failure stages and types. The parameters and formulas are calibrated and adjusted accordingly. It is found that, for short precast columns with GSS connectors, the theoretic solutions are within 5% in difference compared with test results, which shows better accuracy than other methods. This indicates that the proposed method is effective for the estimation of shear strength in this case.